Problem Based Learning (PBL) in an Infectious Diseases Fellowship. (4th October 2017) - Isada, Carlos; Isada, Alex
Abstract: Background: Problem Based Learning (PBL) is an active learning process that adheres to key principles of adult learning theory. PBL is widely used in undergraduate medical education. To our knowledge there have been no published reports of PBL based curricula at the residency/fellowship level. Factors include time and labor for development, scheduling constraints, and competing clinical demands. We describe the implementation of a PBL based curriculum in an ID fellowship and its potential application to the American College of Graduate Medical Education (ACGME) Milestones. Methods: From 2003–5 a PBL-based core curriculum was developed for the ID fellowship at the Cleveland Clinic, replacing a didactic lecture-based curriculum. The PBL group consisted of 6–7 fellows and one preceptor, 2 hours per week. Cases were presented as diagnostic unknowns including radiographs, images, and pathologic materials. Course materials were presented through MOODLE, a web-based, interactive platform. Fellows worked separately and were allowed access to reference materials. Answers were submitted in a standardized short-essay format. For each case, the fellow listed his/her "top 3" differential diagnoses, described the pros and cons for each diagnosis, and then chose the single best answer. "Grade 1" was assigned if the actual diagnosis matched the fellow's top choice; "grade 2" if the actual diagnosis was one of the top 3 diagnoses; grade "3" if the actual diagnosis was not within the top 3. Descriptive statistics and repeated-measures ANOVA was used to analyze test scores. Results: 32 fellows completed the PBL curriculum (2005–2015). Each trainee completed an average of 130 cases. About 60% of cases were derived from the preceptor's patients, the remainder were abstracted from the literature. Year 2 fellows demonstrated significantly more grade 1 and 2 responses compared with Year 1 fellows. Diagnostic accuracy (grade 1 responses) increased for individual trainees when tracked serially over two years. Conclusion: An on-line PBL curriculum can be successfully integrated into an ID fellowship. A simple scoring system can be used to grade PBLs, and track development of medical knowledge and medical decision making, two of the ACGME Milestones. Disclosures: All authors: No reported disclosures.